2020
DOI: 10.3389/fonc.2020.522816
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary Therapy Managed Recurrent Glioblastoma in a BRAF-V600E Mutant Pregnant Female: A Case Report and Review of the Literature

Abstract: Background: Glioblastoma (GBM) is the most malignant intracranial tumor in adults. However, the overall management of GBM in pregnancy is rarely reported. How to balance the therapeutic benefits to the mother and risks to the fetus remains hugely challenging for clinicians. The application of specific targeting therapy combined with conventional treatment sheds light on a longer lifetime for the patients suffering from GBM. Case Presentation: We present a pregnant female at 20 weeks gestation diagnosed with GB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…However, a recent study suggested that a combination of well-circumscribed borders, large cysts, and cortical involvement was more definitive in BRAF-mutant cases rather than the extent of perifocal edemas [31]. Although one patient in our study had multifocal lesions and cases with diagnosis of gliomatosis cerebri harboring a BRAF mutation have been reported [6,29,34], the majority of BRAF-GBMs show a single lesion on MRI [9,20,22,25,29,31].…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…However, a recent study suggested that a combination of well-circumscribed borders, large cysts, and cortical involvement was more definitive in BRAF-mutant cases rather than the extent of perifocal edemas [31]. Although one patient in our study had multifocal lesions and cases with diagnosis of gliomatosis cerebri harboring a BRAF mutation have been reported [6,29,34], the majority of BRAF-GBMs show a single lesion on MRI [9,20,22,25,29,31].…”
Section: Discussionmentioning
confidence: 48%
“…The efficacy of targeting therapy for BRAF V600E using dabrafenib and trametinib have been reported in clinical experiences [16][17][18][19][20][21][22][23][24][25]. To screen the potential targeting therapy candidates for BRAF V600E, clinical sequencing of cancer-associated genes would be the most appropriate approach in clinical practice [26].…”
Section: Introductionmentioning
confidence: 99%
“…Sporadic cases of impressive treatment responses with vemurafenib have been reported, including cases of complete radiological regression of the disease, with prolonged symptomatic control (26)(27)(28).…”
Section: B-raf-inhibitors In Gb: Clinical Evidencesmentioning
confidence: 99%